Q. rotundifolia and p. hybrida pollenextracts induced basophil degranulation: study using a cell line expressing human FcERI - M Antunes, Célia (2017)
Introduction:Currently skin prick test remains the favorite tech-nology in allergy diagnosis to aeroallergens. These tests, however,cause discomfort to the patient. Several biochemical methods basedon IgE analysis are available but have limited diagnostic power asbiological response, hence elicitation of allergic reaction, is not pre-dicted by these tests.Objectives:The aim of this work was to investigate whether abasophil cell line expressing human high affinity IgE receptor (FcERI)is useful as a complementary tool for the evaluation of potentialallergic reaction elicited by novel allergenic species.Results:Pollen extracts from different species were prepared withammonium bicarbonate buffer, lyophilized and stored at 80°C untiluse. A group of selected patients with known allergy to grassesselected to this study and sera was obtained under informed con-sent. Enzymoallergosorbent test (EAST) was performed to character-ize immunoreactivity toDactylis glomerata,Quercus rotundifoliaandPlatanus hybridapollen. Batches of RBL-h21 cells, maintained inadherent culture, were sensitized with human sera (purified IgE wasused as control) and were stimulated with pollen extracts or Anti-IgEantibody. Histamine release (%degranulation) was assessed using aß-hexosaminidase assay.All sera exhibited immunoreactivity againstD. glomerata,Q. rotundi-folia andP. hybridain EAST test. Inhibition analysis evidenced cross-reactivity withD. glomeratain 60% (Q. rotundifolia) and 50% (P.hybrida) cases. Batches of RBL-h21 cells sensitized with pooled serafrom specific (sPool) or cross-reactive (crPool) patients exhibited aselective and dose-dependent degranulation responses upon stimula-tion with pollen extracts in the range of 1-200lg/mL. Maximaldegranulation (>25%) was observed for 50, 120 and 62lg/mL forD.glomerata,Q, rotundifoliaandP. hybridapollen extracts, respectively.Stimulation of sPool cell batches showed dose-response curvesshifted towards lower concentrations (LOEC 6 and 12lg/mL) when compared to crPool (LOEC=24lg/mL) forP. hybridaandQ. rotundi-folia. Similar cell responses toD. glomeratawere observed irrespec-tively of the pool group.Conclusions:These results show that RBL-h21 cells sensitizedwith human sera exhibit specific and dose-dependent degranulationupon stimulation with pollen extract containing allergens suggestingthis bioassay may constitute an useful tool both for research and/ordiagnostics to evaluate potential elicitation of allergic reactions.